Global incidence and prevalence in uveal melanoma - Xincen Hou; Alexander C. Rokohl; Xueting Li; Yongwei Guo; Xiaojun Ju; Wanlin Fan; Ludwig M. Heindl (Advances in Ophthalmology Practice and Research)
Purpose: The most common intraocular cancer in adults is uveal melanoma (UM). This study aimed to investigate and report the incidence and prognosis of UM in different regions of the world. Methods: We retrieved relevant data on UM from the PubMed database and analyzed its global incidence and prognosis. All data was obtained from a national population-based registry, with publication dates ranging from 2013 to 2023. Results: The incidence rates of UM vary across different regions: in the United States, rates were 5.1 per million (1993–2008) and 5.2 per million (1973–2013); in Canada, rates ranged from 3.34 per million (1992–2010) to 5.09 per million (2011–2017); in Republic of Korea, the rate was 0.42 per million (1999–2011); in New Zealand, it was 5.56 per million (2000–2020); in Australia, it was 7.6 per million (1982–2014); and in Europe, rates ranged from 3.1 to 5.8 per million (1995–2002). Among European countries, Sweden (5.6 per million (1960–2009)), Germany (6.41 per million (2009–2015)), Poland (6.67 per million (2010–2017)), and the United Kingdom (10 per million (1999–2010)). Conclusions: The most common site of occurrence for UM is in the choroid. Limited data suggest a stable trend in UM incidence rates across the included countries, but significant differences in incidence rates exist among different countries and regions, with notably lower rates in Asian countries compared to Europe, North America, and Oceania. In general, the incidence rate in males is slightly higher compared to that in females.